Colorectal cancer risk variants rs10161980 and rs7495132 are associated with cancer survival outcome by a recessive mode of inheritance. Issue 11 (23rd January 2021) - He, Yazhou; Timofeeva, Maria; Zhang, Xiaomeng; Xu, Wei; Li, Xue; Din, Farhat V. N.; Svinti, Victoria; Farrington, Susan M.; Campbell, Harry; Dunlop, Malcolm G.; Theodoratou, Evropi
Abstract: Previous studies using additive genetic models failed to identify robust evidence of associations between colorectal cancer (CRC) risk variants and survival outcomes. However, additive models can be prone to false negative detection if the underlying inheritance mode is recessive. Here, we tested all currently known CRC‐risk variants (n = 129) in a discovery analysis of 5675 patients from a Scottish cohort. Significant associations were then validated in 2474 CRC cases from UK Biobank. We found that the TT genotype of the intron variant rs7495132 in the CRTC3 gene was associated with clinically relevant poorer CRC‐specific survival in both the discovery (hazard ratio [HR] = 1.97, 95% confidence interval [CI] = 1.41‐2.74, P = 6.1 × 10 −5 ) and validation analysis (HR = 1.69, 95% CI = 1.03‐2.79, P = .038). In addition, the GG genotype of rs10161980 (intronic variant of AL139383.1 lncRNA) was associated with worse overall survival in the discovery cohort (HR = 1.24, 95% CI = 1.10‐1.39, P = 3.4 × 10 −4 ) and CRC‐specific survival in the validation cohort (HR = 1.26, 95% CI = 1.01‐1.56, P = .040). Our findings show that common genetic risk factors can also influence CRC survival outcome.